Diary of a Williamsburg hostess, which recites the every day events of life in the restored capital of colonial Virginia as seen and recorded by a lady of that city in an entirely fictitious manner so that any resemblance to any individual living or dead which may be fancied by any reader of this chronicle will result in the utmost astonishment to the writer, Helen J. Campbell. Drawings by Alison Mason Kingsbury. (1946)
Summary goes here